The study of disc monopole antenna for partial discharge measurement - Petchphung, Prawit; Leelajindakrairerk, Monthon; Pattanadech, Norasage; Yutthagowith, Pearawut; Aunchaleevarapan, Kraision (My University, 2007)
This paper presents the study of disc monopole antenna for partial discharge measurement. The antenna was studied with computer program and tested. Then it was used for partial discharge measurement of the artificial partial discharge models, corona discharge, surface discharge, and internal discharge. The partial discharge tested results obtained from the designed antenna are relatively similar the tested results obtained from the standard antenna. The tested results show that the designed disc monopole antenna prototype has the good characteristics to measure partial discharge phenomena. It is still improving for high efficiency. © 2007 RPS.
Keywords: Disc monopole antenna; Partial discharge; UHF